Trend of parking demand at Machap Northbound Rest Area - Abd. Wahab, Muhammad Syimir (2015)
Transportation planners need previous information on "Parking Generations" in order to propose new developments and to predict changes in the parking generation. Parking Generations depends on various factors such as number of facility, number of shop, and gross floor area. The Institute of Transportation Engineers (ITE) is an international body of transport professionals based in Washington, DC, USA, that publishes and updates the information on parking generation for various types of land use types in USA. In Malaysia there does not exist any parking generation guideline or handbook that can be used to estimate the parking supply. The main objective of this project is to determine the parking demand at Machap Northbound Rest Area located at Expressway. The study was conducted on different days to allow significant variation of traffic volumes. So that, the relationship between the traffic volume on major road and traffic volume entering the rest area can be determined. Each day have different traffic variation. The parameter used in this study was the vehicular volume on major road (expressway). Parking Generation Guideline by ITE was used to collect Parking demand data. The linear regression between parking demand vehicular volume shown that there is positive relationship with value of R2 equal to 0.95